2010
DOI: 10.1509/jmkr.47.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Compatibility and the Effectiveness of Antidrinking Messages: A Defensive Processing Perspective on Shame and Guilt

Abstract: Five studies examine how the two distinct emotional states of shame and guilt influence the effectiveness of messages that highlight socially undesirable consequences of alcohol consumption. Appeals that frame others as observing versus suffering the negative consequences of binge drinking differentially activate shame and guilt. Given these emotional consequences of message framing, the authors examine the interaction between incidental shame or guilt and message framing on drinking intentions and behavior. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
195
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(209 citation statements)
references
References 18 publications
7
195
4
3
Order By: Relevance
“…They both focus on the role of the self within a broader social context (Agrawal & Duhachek, 2010, p. 264), that is, guilt-and shame-driven behavior is triggered by social factors. Both guilt (Burnett & Lunsford, 1994) and shame (Bagozzi, 2006) have recently been shown to be influential in marketing (Agrawal & Duhachek, 2010;Duhachek, Agrawal, & Han, 2012). Guilt is the sense of being accountable for violating internal standards (English & Macker, 1976;Stein, 1968).…”
Section: Resultsmentioning
confidence: 99%
“…They both focus on the role of the self within a broader social context (Agrawal & Duhachek, 2010, p. 264), that is, guilt-and shame-driven behavior is triggered by social factors. Both guilt (Burnett & Lunsford, 1994) and shame (Bagozzi, 2006) have recently been shown to be influential in marketing (Agrawal & Duhachek, 2010;Duhachek, Agrawal, & Han, 2012). Guilt is the sense of being accountable for violating internal standards (English & Macker, 1976;Stein, 1968).…”
Section: Resultsmentioning
confidence: 99%
“…Haidt 2003;Tangney et al 2007), or in consumer behavior (e.g., Agrawal and Duhachek 2010;Kim and Johnson 2013;Peloza et al 2013), this research is the first that determines how guilt and pride experienced after a consumption episode can regulate the purchase of sustainable alternatives.…”
Section: Discussionmentioning
confidence: 97%
“…This negative emotion leads consumers to regulate their own choices to avoid feeling guilty (Mellers and McGraw 2001). Guilt reinforces self-regulation in relation to over-eating and vice food consumption (Mishra and Mishra 2011;Mohr et al 2012), can be effectively used in anti-drinking campaigns (Agrawal and Duhachek 2010;Duhachek et al 2012), promotes social issues through cause-related marketing (Kim and Johnson 2013), and supports fairer negotiation strategies (Cohen 2010). Researchers also study guilt's ability to promote charitable giving (Basil et al 2006(Basil et al , 2008Hibbert et al 2007).…”
Section: How Self-conscious Emotions Regulate Sustainable Consumptionmentioning
confidence: 99%
“…Prior research has suggested that processing a high-risk health message presents a trade-off between long-term benefits and shortterm interests. Although individuals at high risk for a disease can improve their long-term well-being by taking preventative actions, recognizing risk leads to emotional deterioration in the short run (Agrawal and Duhachek 2008;Agrawal and Menon 2008;Agrawal, Menon, and Aaker 2007;Keller, Lipkus, and Rimer 2003;Menon et al 2007). In addition, health decisions might be laden with emotionally difficult trade-offs between making a decision that will help reduce emotional anguish and one that will benefit longterm health (Kahn and Luce 2003).…”
Section: Health Messages and Depletion Effectsmentioning
confidence: 99%